Leisure, gender and poverty : working-class culture in Salford and Manchester, 1900-1939 - "Davies, Andrew" (Philadelphia, 1992)
In this vivid and detailed account of everyday life in two cities, Andrew Davies challenges many of the assumptions which have dominated historical approaches to 'traditional working-class culture in Britain. Vibrant oral testimonies are used to explore a world of Whit walks and monkey parades:; cinemas and dance halls; street singers and Saturday night markets; comer gangs and police harassment: back street bookmakers and drinking on the slate; and fortune-telling and spiritualism. He shows how leisure activities were heavily structured and constrained by poverty and unemployment, and patterned by gender and generation. The separate experiences of men and women, and a distinct youth culture, are highlighted in a path-breaking examination of the diversity of working class culture. Paying particular attention to Salford (home of The Classic Slum. Love on the Dole and L.S. Lowry), this book will be of interest to historians and sociologists concerned with working-class experience in twentieth-century Britain.
Keywords: Working Class England Manchester History 20th century